Activation of beta 1 but not beta 3 integrin increases cell traction forces. Issue 6 (8th February 2013) - Lin, Grace L.; Cohen, Daniel M.; Desai, Ravi A.; Breckenridge, Mark T.; Gao, Lin; Humphries, Martin J.; Chen, Christopher S.
Abstract : Cell‐generated traction forces induce integrin activation, leading to focal adhesion growth and cell spreading. It remains unknown, however, whether integrin activation feeds back to impact the generation of cytoskeletal tension. Here, we used elastomeric micropost arrays to measure cellular traction forces in wildtype and integrin‐null cells. We report that activation of β1 but not β3 integrin, by either increasing density of immobilized fibronectin or treating with manganese, elicited fibroblast spreading and cytoskeletal tension. Furthermore, this force generation required Rho kinase and myosin activity. These findings suggest that integrin activation and cell traction forces comprise a bi‐directional signaling unit of cell adhesion. Abstract : ► Integrin activation induces cell spreading and cytoskeletal tension. ► Elastomeric micropost arrays report integrin activation‐mediated traction forces. ► Activation of β1 integrin but not β3 integrin drives cell traction forces.